ISOSTATIC PROCESSES AND INTRACONTINENTAL OROGENESIS - Artemjev M.E.; Kaban M.K. (My University, 1991)
At present, there are two concepts of the term isostasy. According to the first one, isotasy means hydrostatic pressure conditions at the depth of compensation existing due to mass distributions above that depth. The second concept implies the existence of hydrostatic pressure at the depth of compensation without any limitation in the way these conditions are reached. In this case, isostasy is identical with mechanical equilibrium.Isostatically compensated models of different types of mountain areas (exemplified by the Causasus and the Tien Shan) have been constructed and analysed. In the Alpine mountain ridges, local isostasy takes place as a rule due to a corresponding mass distribution in the Earth's crust. The mountain ridges formed by neotectonic activation are also locally compensated, but from 40 to 50% of the compensation is provided by some low-density material of the subcrustal layer. Disregarding data concerning crustal and lithospheric inhomogeneities, as well as narrow classes of the models under consideration, may often lead to false conclusions about the elastic thickness of the lithosphere. A high velocity of isostatic readjustment movements and a predominance of local but different types of compensation indicate that the rigidity of the lithosphere is usually overestimated and that the significant differences of crustal structure and subcrustal density inhomogeneities are typical of two principal types of intracontinental orogeny.